2022
DOI: 10.3390/coatings12030332
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Study on Fretting Tribological Behavior of Composite Lubrication Structure on the Titanium Alloy Surface

Abstract: As an excellent light metal material, titanium alloy has an important application in high technology equipment. In this study, the composite lubrication structure was prepared on the titanium alloy surface by combining the surface texture, thermal oxidation layer, and polytetrafluoroethylene(PTFE)-based lubricating coating. The effect of texture parameters and thermal oxidation layer on the fretting wear behavior of the composite lubrication structure was evaluated under a load of 50 N. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Liquid metal (LM) lubricants [81,[117][118][119], nanoparticle oil lubricants [119][120][121][122][123], solid lubricants [32,[124][125][126][127][128][129][130][131], and water lubricants [41,76,[132][133][134] have all recently exhibited fascinating behavior in overcoming the traditional oil lubricants' limitations. The mechanisms of these lubricants can be shown in Figure 10.…”
Section: Effect Of Surface Texture On Lubricated Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid metal (LM) lubricants [81,[117][118][119], nanoparticle oil lubricants [119][120][121][122][123], solid lubricants [32,[124][125][126][127][128][129][130][131], and water lubricants [41,76,[132][133][134] have all recently exhibited fascinating behavior in overcoming the traditional oil lubricants' limitations. The mechanisms of these lubricants can be shown in Figure 10.…”
Section: Effect Of Surface Texture On Lubricated Conditionmentioning
confidence: 99%
“…In addition, Profito et al [31] showed that the operating lubrication regime was the main factor for friction reduction. On the other hand, Ma et al [32] combined surface texture, thermal oxidation, and a Polytetrafluoroethylene (PTFE)-based lubricant coating. The results revealed that PTFE boosted with thermal spraying on the surface texture improved the tribological performance.…”
Section: Introductionmentioning
confidence: 99%
“…Lubrication strategies such as the surface modification of artificial implants or the usage of fluid or hydrogel lubricants , have already been investigated in the literature. However, the application of these methods has shown limited success related to the resulting friction and wear reduction.…”
Section: Introductionmentioning
confidence: 99%
“…14 Solid lubricants can be filled into textured surfaces to exert the antifriction performance of the solid lubricant and enhance the friction and wear properties of the textured surface. 15,16 Textured surfaces filled with PTFE have some applications, such as compressor blades, 17 guide rails, and bearings. 18 For example, Wu et al 19 showed that filling molybdenum disulfide into the groove texture of cemented carbide surfaces can reduce the surface COF by 20%-25%.…”
Section: Introductionmentioning
confidence: 99%